2007
DOI: 10.1007/s00405-007-0449-z
|View full text |Cite
|
Sign up to set email alerts
|

Gel chromatographic characterization of proteins in mucous and serous middle ear effusions of patients with otitis media in comparison to serum proteins

Abstract: Otitis media with effusion (OME) is an inflammatory disease of the middle ear cavity that is associated with middle ear effusions (MEEs), which are frequently mucous and serous for pediatric and adult patients exhibiting low and high responsiveness to medical treatment, respectively. To assess the pathological outcomes in mucous and serous MEEs, their protein compositions were determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blotting in comparison with those in the same patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However the mucin quantification approach employed (periodic acid-Schiff, PAS) was not specific to mucins. Collecting and analyzing 25 mucoid MEEs and 30 serous MEEs, Yabe et al ( 40 ) showed 60% of the proteins of mucoid MEEs were mucins but not for serous samples. In contradistinction to our findings, their serous samples showed less IgA, IgG and lysozyme than mucoid ones.…”
Section: Discussionmentioning
confidence: 99%
“…However the mucin quantification approach employed (periodic acid-Schiff, PAS) was not specific to mucins. Collecting and analyzing 25 mucoid MEEs and 30 serous MEEs, Yabe et al ( 40 ) showed 60% of the proteins of mucoid MEEs were mucins but not for serous samples. In contradistinction to our findings, their serous samples showed less IgA, IgG and lysozyme than mucoid ones.…”
Section: Discussionmentioning
confidence: 99%
“…Smallvolume, clinically unapparent effusions may be found at tympanocentesis [Paradise et al, 1976;Orchik et al, 1978;Fiellau-Nikolajsen, 1983;Karma et al, 1989;Toner and Mains, 1990;Babonis et al, 1991;Finitzo et al, 1992;Ovesen et al, 1993;Sassen et al, 1994;van Balen and de Melker, 1994;Watters et al, 1997]. In OME, effusions may be serous or mucoid [Carrie et al, 1992]; the former are mucin poor and associated with less inflammation in terms of immunoglobulin and cytokine levels [Chung et al, 2002;Yabe et al, 2008] and leucocyte infiltration [Tanaka et al, 1986;Yoon et al, 1990] (and are more often of shorter duration [Yoon et al, 1990], unilateral, and in an older age group [Giebink et al, 1982a, b]). …”
Section: Pathological Analysesmentioning
confidence: 99%